Winning back dad - Bone, Ian; Smith, Craig (Walker Books London, 2000)
Kel's Dad has had to sell his truck and stay home to look after Kel and his little sister, while Mum goes out to work. The King of the Road becomes the King of the Grumps, but a competition at the District Show gives Kel a great idea for solving the problem. Suggested level: primary